HTTP blocking in IR: bbc.com, facebook.com, signal.org, youtube.com (Iran) - Voidly (2026)
CRITICAL severity censorship detected in Iran. Confidence: 85%. Data sourced from CensoredPlanet.
Censorship Incident ID: IR-2026-0012
Keywords: censorship; IR; censorship; critical